2020
DOI: 10.1016/j.eclinm.2020.100564
|View full text |Cite
|
Sign up to set email alerts
|

Parental mental health before and during pregnancy and offspring birth outcomes: A 20-year preconception cohort of maternal and paternal exposure

Abstract: Background Preterm birth (PTB) and small for gestational age (SGA) are increasingly prevalent, with major consequences for health and development into later life. There is emerging evidence that some risk processes begin before pregnancy. We report on associations between maternal and paternal common mental disorders (CMD) before and during pregnancy and offspring PTB and SGA. Methods 398 women with 609 infants and 267 men with 421 infants were assessed repeatedly for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
10
1
Order By: Relevance
“…[ 22 28 29 ] Study by Spry et al ., 2020 found association of CMDs during pregnancy with prematurity but not with low birth weight. [ 40 ] In the present study, we did not find any significant association of CMDs with child health outcomes. Majority of the pregnant women in our study were living in extended family.…”
Section: Discussioncontrasting
confidence: 77%
“…[ 22 28 29 ] Study by Spry et al ., 2020 found association of CMDs during pregnancy with prematurity but not with low birth weight. [ 40 ] In the present study, we did not find any significant association of CMDs with child health outcomes. Majority of the pregnant women in our study were living in extended family.…”
Section: Discussioncontrasting
confidence: 77%
“…Comorbidity is common for mental disorders (7,8). The poor preconception of mental health is a risk factor for both pregnancy complications and adverse health outcomes in the offspring (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, pregnancy complications were identified in four out of ten women (10). Studies, including both primiparous and multiparous women, show that women with preconception common mental disorders (CDM, i.e., depression and anxiety) are more likely to have pregnancy complications, such as gestational diabetes mellitus (GDM), miscarriage or stillbirth, and delivery of a preterm or a low-birthweight newborn (9)(10)(11). A recent systematic review and meta-analysis show that antenatal maternal anxiety was associated with preterm birth and low birthweight, but not with pre-eclampsia, and cesarean delivery (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most evidence is based on animal models, and a few recent studies suggested that the paternal preconception environment, such as diet and early-life stress or trauma plays a role in foetal development and offspring health outcomes [69][70][71][72][73]. A handful of human studies have shown links between paternal alcohol consumption, smoking and mental health in the preconception period with birth outcomes [66,74,75], although in some cases the evidence is mixed [74]. Several studies have demonstrated that paternal health status is linked with preterm birth and low birth weight in the child, as well as gestational diabetes and preeclampsia in the mother [76,77].…”
Section: Introduction 1rationalementioning
confidence: 99%